A survey of the needs and problems of the novices of the Order of St. Gabriel as basis for a proposal of pastoral guidance program - Ezhanikatt, Jacob (Animo Repository, 1978)
This study surveyed the needs of the novices of the Brothers of St. Gabriel in India together with their present-day problems in the light of Vatican II as a basis for the pastoral guidance program. The descriptive research design method was used in the study. The subjects were the novices of the brothers of St. Gabriel at Yercaud in India. Respondents totaled 66 consisting of all the 60 novices whose ages ranged from 18 to 25 and the 6 staff of the novitiate whose ages ranged from 25 to 40. The problem checklist which was an adaptation of the Moony Problem Checklist was administered to the novices. It consisted of 30 problems categorized into 10 areas. Questionnaire I was served to the novices to find out the necessity of guidance and counseling program in the novitiate. Questionnaire II was also served to the members of the staff to find out the extent they felt the need of an organized guidance program. The questionnaires were adopted from Nidini (1975). From this study, the following conclusions were derived : 1. From the problem checklist survey, the nature of the problems faced by the novices were : Personal psychological relations, Social personal relations, Moral and religion, adjustment to school work, Curriculum and teaching procedures, Health and physical development, and Social recreational activities. 2. The then formation program provided to a certain extent, some help to meet some of the needs of the novices. However, they can be better organized and modified in the light of the answers given in the questionnaires, served both to the novices and to the members of the staff. 3. There was an openness on the part of the novices to discuss their problems with their superiors especially a trained counselor. 4. The survey indicated the fact that individual and group counseling could be incorporated into the program of the formation of the novices. 5. The members of the staff expressed their earnest wish to integrate an organized guidance program to the total formation program.